(untitled) (Journal of Advanced Veterinary and Animal Research, 2014)
The aim of this study was to determine the reproductive parameters of sows in selected area of Bangladesh. A total of 51 sows from 21 farms were selected for this study. The data on reproductive parameters were collected from the owners by interviewing with pretested questionnaire. We found that the age at puberty, estrus cycle length, estrus duration, interval between farrowing and onset of estrus and gestation length were 254.5±34.4 and 21.2±1.2 days, 34.2±13.2 h, 51.8±10.9 and 114.3±0.9 days, respectively. The number of required services for each pregnancy in native sows was 1.4 ±0.6, and the first service pregnancy rate using natural mating was 63.8%. Moreover, the number of piglets born per sow was 7.6±3.4. The highest piglet production (10.6±3.1) was in parity 5 and the lowest (4.1±0.6) was in parity 1. Estrus was detected in 34.1% sows on the basis of observing standing reflex when boar mounted. In conclusion, reproductive parameters in native sows of Bangladesh need to be improved for ensuring satisfactory reproductive performances. http://dx.doi.org/10.5455/javar.2015.b55